Evaluation of the Effectiveness of Patient-Centered Care on Patient Engagement in Hospital Care - Al'amri, Magfirah (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to evaluate the effectiveness of patient-centered care (PCC) in enhancing patient engagement during hospital care. The background of this research stems from the growing demand for healthcare systems that respect patients as individuals with unique needs, values, and preferences. Although the concept of PCC has been widely adopted, its implementation often varies and has not consistently demonstrated tangible impacts on improving patient participation. This research uses a qualitative approach with a literature review design, analyzing scholarly sources from databases such as Google Scholar, PubMed, Scopus, and ScienceDirect. Data were analyzed using thematic content analysis to identify core themes describing the relationship between PCC implementation and patient engagement. Findings reveal that PCC consistently contributes to higher levels of engagement through four key aspects: shared decision-making, effective communication, emotional support, and information transparency combined with patient education. Comprehensive implementation of PCC fosters patients’ sense of autonomy, satisfaction, and trust in healthcare providers. Consequently, PCC proves to be not only an ethical framework but also a practical strategy to improve clinical outcomes and strengthen the patient-provider partnership. The study emphasizes the importance of empowering healthcare workers with empathetic communication and collaborative skills while creating supportive hospital environments that enable patients to actively participate in their care.